Hubungan Tingkat Pengetahuan tentang Metode KB Efektif dengan Penggunaan Metode KB Efektif pada Wanita Usia Subur di Dusun Kebur Argomulyo Cangkringan Sleman Yogyakarta - Marliyani, Rina (STIKES 'Aisyiyah Yogyakarta, 2008)
One of the main policies in the national family planning program in Indonesia is to attempt all families to have maximum of 2 children, by using the most effective family planning method to limit their fertility. Based on the population census in 2000, the growth number in Indonesia was still relatively high, that is, 1.38% per year. Sleman region with the population of 913.397 people, with the active family planning users of 65,43%. The target that was intended to achieve was the users of the effective family planning in PUS in Sleman region can increase by 80%. This research was intended to identify the correlation between the knowledge level of the effective family planning method and the application of the effective family planning method. This research was correlation descriptive one with the approach of cross sectional time. The subjects of the research were PUS. The technique of choosing samples in this research was purposive sampling, and the data was analyzed by the statistical test of chi square. The result of the research showed that there was no correlation between the knowledge level on the effective family planning method and the application of the effective family planning method in village Kebur. The research showed that the respondents with good knowledge were 28 people or 65,1%. The data analysis conducted using Chi Square showed that the countX2 was 1,835, p value = 0,400, which meant there was no correlation between the knowledge level on the effective family planning method and the application of the method on the fertile women in village Kebur. For further research, if anyone wants to do the same research with the same title, it is suggested to change the research method.